1969
DOI: 10.1063/1.1652866
|View full text |Cite
|
Sign up to set email alerts
|

Bistable Optical Element and Its Applications

Abstract: Optical resonators containing saturable absorbers (saturable resonators) have nonlinear characteristics and can exhibit hysteresis. This is demonstrated experimentally at 10.6 μ wavelength. A saturable resonator is used to switch out the CO2 laser light from its cavity and for repetitive Q-switching. Devices are described to obtain variable length pulses, infinite pulse trains, logical operations on two signals, and memory functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
108
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(110 citation statements)
references
References 4 publications
0
108
0
2
Order By: Relevance
“…Because of its underlying nature and possible applications in the field of all-optical processing, optical bistability (OB) has been a subject of intense experimental and theoretical research . In early studies the use of a saturable absorber to induce OB was suggested [3][4][5][6][7]. The phenomenon was demonstrated experimentally for a cell of sodium vapor enclosed in a Fabry Perot interferometer and excited by a cw dyelaser [8].…”
mentioning
confidence: 99%
“…Because of its underlying nature and possible applications in the field of all-optical processing, optical bistability (OB) has been a subject of intense experimental and theoretical research . In early studies the use of a saturable absorber to induce OB was suggested [3][4][5][6][7]. The phenomenon was demonstrated experimentally for a cell of sodium vapor enclosed in a Fabry Perot interferometer and excited by a cw dyelaser [8].…”
mentioning
confidence: 99%
“…This is observed as a hysteresis cycle in the plot of the output light intensity versus input light intensity. Optical bistability was proposed by [1][2][3] and since then observed in many different systems such as cavity lasers [4][5][6][7], atomic systems [7,8], semiconductors [9][10][11], and microcavity polaritons [12,13]. Bistability is commonly used for device applications [3,[14][15][16], particularly in polariton systems as spin switch and optical memory [17,18], optical transistor [19], laser [20], and logic functions [21].…”
Section: Introductionmentioning
confidence: 99%
“…All-optical arrays as potential memory devices [19] have intrigued physicists since the first observation of optical bistability [17]. (For background material see, for example, [1,9,16].)…”
Section: Introductionmentioning
confidence: 99%